Conservation agriculture and drought-tolerant germplasm: Reaping the benefits of climate-smart agriculture technologies in central Mozambique - Thierfelder, Christian L.; Rusinamhodzi, Leonard; Setimela, Peter; Walker, Forbes; Eash, Neal S. (Cambridge University Press, 2016)
Conservation agriculture (CA) based on minimum soil disturbance, crop residue retention and crop rotations is considered as a soil and crop management system that could potentially increase soil quality and mitigate the negative effects of climate variability. When CA is combined with drought-tolerant (DT) maize varieties, farmers can reap the benefits of both—genetic improvement and sustainable land management. New initiatives were started in 2007 in Mozambique to test the two climate-smart agriculture technologies on farmers' fields. Long-term trends showed that direct seeded manual CA treatments outyielded conventional tillage treatments in up to 89% of cases on maize and in 90% of cases on legume in direct yield comparisons. Improved DT maize varieties outyielded the traditional control variety by 26–46% (695–1422 kg ha−1) on different tillage treatment, across sites and season. However a direct interaction between tillage treatment and variety performance could not be established. Maize and legume grain yields on CA plots in this long-term dataset did not increase with increased years of practice due to on-site variability between farmer replicates. It was evident from the farmers' choice that, beside taste and good milling quality, farmers in drought-prone environments considered the potential of a variety to mature faster more important than larger potential yields of long season varieties. Population growth, labor shortage to clear new land areas and limited land resources in future will force farmers to change toward more permanent and sustainable cropping systems and CA is a viable option to improve their food security and livelihoods.